PENYIMPANGAN SEKSUAL: LGBT PADA KELUARGA MUSLIM, FAKTOR, DAN SIKAP ISLAM - Salma Nuha Ghufron; Muhamad Arifin (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2023)
LGBT (Lesbian, Gay, Bisexual and Transgender) is a social phenomenon in society. Along with the flow of globalization and the rapid development of information technology, this community has begun to show its existence in Indonesia. The existence of this community raises the pros and cons in society. Initially, they chose to hide their identities, but over time and changes in people's perspectives, this community has begun to dare to expose their identities and demand recognition from the public. The behavior of this community is not in line with the teachings of Islam and the culture of society that has been ingrained since ancient times. This research was conducted on the LGBT community in South Jakarta from various walks of life and various walks of life. This study aims to analyze the factors that cause sexual deviation: LGBT, as well as Islamic views in responding to it. This study uses a qualitative method with a case study research type. The results of this study indicate that: (1) there are 4 factors that cause sexual deviation: LGBT, (2) the dominant factor that causes sexual deviation: LGBT is the factor of being a victim of sexual harassment, and (3) Islamic views in addressing this phenomenon.